Differential Effects of Hunting on Populations of Hornbills and Imperial Pigeons in the Rainforests of the Eastern Indian Himalaya - Dasgupta, Soumya, Hilaluddin (Indian Forester, 2012)
Responses of hornbills and Ducula pigeons to hunting and disturbances to their habitats may help us understand the implications for the regeneration of their dependent tropical forest trees. Moreover, density estimates serve as a gauge of whether some frugivorous birds can potentially substitute for the decline of their functionally-similar competitors. We carried out a October long survey of 24 line-transects distributed across disturbed (2 sites) and undisturbed (4 sites) habitats in the lowland evergreen forests of Pakke wildlife sanctuary and surrounding forests of Arunachal Pradesh. Hornbill and Ducula densities were estimated with DISTANCE. While densities of the Great Indian Hornbill, Buceros bicornis; Oriental Pied Hornbill, Anthracoceros albirostris, and wreathed hornbill, Aceros undulatus were substantially reduced in disturbed habitats, densities of the mountain imperial pigeon, Ducula badia and the green imperial pigeon, Ducula aenea were unaffected. These results suggest that Ducula pigeons may potentially provide substitute dispersal services for large-seeded tree species in disturbed sites, but that this response is most likely context driven.